An Update of Foot and Ankle Fellowship Website Content and Accessibility. Issue 4 (22nd October 2020) - Khwaja, Ansab M.; Du, Peter Z.; Sherman, Nathan; Truchan, Lisa
Category: Other; Ankle Introduction/Purpose: The internet is one of the first resources for prospective fellowship applicants, and a previous study evaluated the presence of information present on foot and ankle websites. This study aims to evaluate the accessibility provided via the American Orthopaedic Foot & Ankle Society (AOFAS) websites and individual websites. Methods: The AOFAS website was used to identify the list of foot and ankle fellowship programs. The database information was used to review links to fellowship program websites and corroborate it with accessibility through a Google search. Information from fellowship program websites and the AOFAS was used to analyze the presence of previously described recruitment and educational content, and this analysis was compared to previously reported metrics. Results: Forty-eight orthopaedic foot and ankle fellowship programs were identified. The AOFAS database featured direct links to 19 (40%) fellowship websites with the Google search providing direct links to 35 (73%) websites. From the available program websites, the most common recruitment content was salary/benefits, faculty listing, program contact information (48, 100%), and program description (47, 98%). The most common educational content was presence of research component (44, 92%) and description of rotations/curriculum (43, 90%). Foot and ankle fellowship information markedly improved in domains of salary/benefits, program description, faculty listing meetings/courses, rotations/curriculum, and had less information in the domains of office/clinic information and operative experience. Conclusion: There continues to be substantial variability between foot and ankle fellowship websites and the AOFAS website regarding program content and descriptions. Some information is more readily available, but other domains have less information now than in previously reported research.